Perception-action in children with ASD - Von Hofsten, Claes; Rosander, Kerstin (Frontiers in Integrative Neuroscience, 2012)
How do disturbances to perception and action relate to the deficiencies expressed by children with autism? The ability to predict what is going to happen next is crucial for the construction of all actions and children develop these predictive abilities early in development. Children with autism, however, are deficient in the ability to foresee future events and to plan movements and movement sequences. They are also deficient in the understanding of other people’s actions. This includes communicative actions as they are ultimately based on movements. Today there are two promising neurobiological interpretation of ASD. First, there is strong evidence that the Mirror Neuron System (MNS) is impaired. As stated by this hypothesis, action production and action understanding are intimately related. Both these functions rely on predictive models of the sensory consequences of actions and depend on connectivity between the parietal and pre-motor areas. Secondly, action prediction is accomplished through a system that includes a loop from the posterior parietal cortex through the cerebellum and back to the premotor and motor areas of the brain. Impairment of this loop is probably also part of the explanation of the prediction problems in children with ASD. Both the cortico-cerebellar loop and the MNS rely on distant neural connections. There are multiple evidence that such connections are weak in children with autism.